Relationship between Serum and Brain Carotenoids, α-Tocopherol, and Retinol Concentrations and Cognitive Performance in the Oldest Old from the Georgia Centenarian Study - Elizabeth J. Johnson; Rohini Vishwanathan; Mary Ann Johnson; Dorothy B. Hausman; Adam Davey; Tammy M. Scott; Robert C. Green; L. Stephen Miller; Marla Gearing; John Woodard; Peter T. Nelson; Hae-Yun Chung; et al. (Journal of Aging Research, 2013)
Oxidative stress is involved in age-related cognitive decline. The dietary antioxidants, carotenoids, tocopherols, and vitamin A may play a role in the prevention or delay in cognitive decline. In this study, sera were obtained from 78 octogenarians and 220 centenarians from the Georgia Centenarian Study. Brain tissues were obtained from 47 centenarian decedents. Samples were analyzed for carotenoids, α-tocopherol, and retinol using HPLC. Analyte concentrations were compared with cognitive tests designed to evaluate global cognition, dementia, depression and cognitive domains (memory, processing speed, attention, and executive functioning). Serum lutein, zeaxanthin, and β-carotene concentrations were most consistently related to better cognition (P<0.05) in the whole population and in the centenarians. Only serum lutein was significantly related to better cognition in the octogenarians. In brain, lutein and β-carotene were related to cognition with lutein being consistently associated with a range of measures. There were fewer significant relationships for α-tocopherol and a negative relationship between brain retinol concentrations and delayed recognition. These findings suggest that the status of certain carotenoids in the old may reflect their cognitive function. The protective effect may not be related to an antioxidant effect given that α-tocopherol was less related to cognition than these carotenoids.